The effects of fatigue on synergy of selected lower limb muscles during running - Hajiloo, Behrouz; Anbarian, Mehrdad; Esmaeili, Hamed; Mirzapour, Mahdi (Journal of biomechanics, 2020)
The purpose of this study was to investigate the effect of fatigue on selected lower extremity muscles synergy during running using non-negative matrix factorization algorithm method. Sixteen male recreational runners participated in this study. The surface electromyographic activity of rectus femoris (RF), vastus lateralis (VL), vastus medialis (VM), biceps femoris (BF), semitendinosus, gastrocnemius medialis (GM), soleus (SO) and tibialis anterior (TA) were recorded on treadmill at 3.3 m s−1 before and after the fatigue protocol. Synergy pattern and relative muscle weight were calculated by non-negative matrix factorization (NNMF) algorithm method. The results showed that using the VAF method, five muscle synergies were extracted from the emg data during running. After the fatigue, the number of muscular synergies did not show a change, but relative weight of the muscles changed. Fatigue did not have any effect on the structure of muscular synergy, but changed the relative weight of muscles. These changes could be the strategy of the central nervous system to maintain optimal function of the motor system.